A retrospective look at global recessions and modern trends in the world economic growth - E. N. Smirnov (Вестник университета)
The aim of the study is to analyze the dynamics of global recessions and world economic growth trends in recent decades in order to identify their main determinants and specifics in the context of the world economy dynamics. The article provides a systematization and classification of the global economic growth stages in retrospect, as well as a comparison of current trends in the development of the world economy with previous global crises. It has been established that the current conditions for the crises’ overcoming are significantly different from those conditions that were observed 40 years ago. It is shown, that in recent decades global crises have become cascading and have a greater impact on the volatility of world markets, making inflationary shocks sharper, and the monetary policy of countries and global financial conditions tougher.